2017
DOI: 10.5897/ajbm2017.8265
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Facebook usage on employee productivity: A case of university of cape coast staff

Abstract: The rapidity in the rise of social media is changing how organizations operate and handle their communication. Several organizations are in search of ways to seize advantage in this emerging era marked by greater real time, interactivity and transparency. The new media, of which Facebook is part, is growing so fast that it makes it imperative for employees to embrace the medium in the workplace. Facebook's widespread among workers has given an interest in how Facebook usage is related to the output of workers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Social networking sites and social media are closely similar, which provide a platform where students can interact, communicate, and share emotional intelligence and looking for people with other attitudes (Gikas & Grant, 2013). Facebook and YouTube channel use also increased in the skills/ability and knowledge and outcomes (Daniel, Isaac, & Janet, 2017). It was highlighted that 90% of faculty members were using some sort of social media in their courses/ teaching.…”
Section: Research Background and Hypothesesmentioning
confidence: 99%
“…Social networking sites and social media are closely similar, which provide a platform where students can interact, communicate, and share emotional intelligence and looking for people with other attitudes (Gikas & Grant, 2013). Facebook and YouTube channel use also increased in the skills/ability and knowledge and outcomes (Daniel, Isaac, & Janet, 2017). It was highlighted that 90% of faculty members were using some sort of social media in their courses/ teaching.…”
Section: Research Background and Hypothesesmentioning
confidence: 99%
“…21 The use of Facebook by employees during working hours can have serious consequences if appropriate measures are not taken to monitor their abuse. 22 Facebook usage helps improve psychological well-being. 23 Job satisfaction and Facebook usage are also found positively correlated among employees.…”
Section: Social Mediamentioning
confidence: 99%
“…SNSs have increased the productivity of employees by facilitating them to learn new skills and knowledge through friends and colleagues available online (Arslan & Zaman, 2015). According to various studies and surveys, employees using SNSs have found to be nine percent more productive than those who do not (Adzovie, Nyieku, & Keku, 2017;David Mielach, 2012;Magnier-Watanabe, Yoshida, & Watanabe, 2010). A study conducted by the Pew Research Centre showed that 20 percent of the employees used SNSs to solve problems at work, and 12 percent asked work-related questions from peers working outside the organization (PWE, 2016).…”
Section: Snss and Productivitymentioning
confidence: 99%